Aligning financial and technical procedures for the determination of urban drainage assets' current and replacement values. Issue 7 (27th June 2022) - Brito, Rita S.; Martinho, M. C.; Almeida, M. C.; Fernandes, M.; Ferreira, S.
Abstract: The paper presents a method for aligning the relevant financial and technical procedures for determining drainage assets' current and replacement values. This alignment is especially pertinent when actual construction costs are unavailable and records in different utility departments (technical and accounting) do not correspond. The current asset value is grounded in estimated construction costs, considering accounting and technical useful lives. Asset portfolio considers the assets providing adequate service quality, regardless of their age. The methodology relies on the update of the assets' registry (updating the assets' value), the increase of the accounting useful life in line with technical practice (reducing annual depreciation), and the accumulated depreciation reversion (increasing net current value). In the case study, the need to update information exchange and align technical and financial procedures in Lisbon Municipality was triggered by internal policy requirements concerning the simultaneous development of the urban drainage asset management plan and the requirement to standardize the accounting system. The application of the methodology led to an increase of approximately five times the assets' current value. The results, their implications, and replicability opportunities are discussed. HIGHLIGHTS: Procedure for aligning financial and technical procedures. The current asset value assessed based on estimated construction cost curves. Consideration of every asset providing good quality service, regardless of their accounting useful life. Graphical Abstract